Swiftwater enemies - Winters, Danica (Winters, Danica. Big Sky search and rescue., 2024)
"The last thing Detective Leo West needs is a tourist telling him how to do his job, even a tourist who claims to be a search-and-rescue pro. Once he sees Aspen Stevens in action, though, he discovers that she's as capable as she is gorgeous. As lies and raging water swirl around them, they have no choice but to trust each other -- while resisting an off-limits attraction." --Page 4 of cover.